Demographic and microbiological characteristics of tuberculous lymphadenitis and other extrapulmonary tuberculosis cases - ERTÜRK ŞENGEL, BUKET (My University, 2022)
Objective: Tuberculosis (TB) is a significant public health problem that remains important worldwide. This study aimed to examine the demographic characteristics and clinical features of patients with extrapulmonary tuberculosis (EPTB) and also identify the comorbidities of EPTB. Our secondary aim was to compare tuberculous lymphadenitis (TBL) with other forms of EPTB.
Keywords: Tıp; Sağlık Bilimleri; Temel Tıp Bilimleri; Medicine; Health Sciences; Fundamental Medical Sciences; TIP, GENEL & DAHİLİ; Klinik Tıp; Klinik Tıp (MED); MEDICINE, GENERAL & INTERNAL; CLINICAL MEDICINE; Clinical Medicine (MED); Genel Sağlık Meslekleri; Patofizyoloji; Temel Bilgi ve Beceriler; Değerlendirme ve Teşhis; Dahiliye; Aile Sağlığı; Tıp (çeşitli); Genel Tıp; General Health Professions; Pathophysiology; Fundamentals and Skills; Assessment and Diagnosis; Internal Medicine; Family Practice; Medicine (miscellaneous); General Medicine; Extra pulmonary tuberculosis; Tuberculous lymphadenitis; Mycobacterium tuberculosis; RISK-FACTORS; CHALLENGES; DIAGNOSIS; PULMONARY